Water Carcinogenicity and Prevalence of HPV Infection in Esophageal Cancer Patients in Huaihe River Basin, China - Maliha Ghaffar; Jintao Li; Lei Zhang; Sara Khodahemmati; Minglian Wang; Yangjunqi Wang; Lijiao Zhao; Runqing Jia; Su Chen; Yi Zeng (Gastroenterology Research and Practice)
Objective. The incidence of the upper gastrointestinal tumor has increased rapidly during recent decades. The relationship between local water pollution and the tumor is still not much clear, so this study was conducted to further investigate the local water pollution and its influence on the malignant cell transformation. Prevalence of human papillomavirus (HPV) in local esophageal cancer (EC) patients was also analyzed in Shenqiu County for the first time. Methods. Two-step cell transformation was used to study different sources of water in the malignant cell transformation, and the existence of 3-methylcholanthrene (3-MC) in water was analyzed from the river and shallow and deep wells. HPV DNA in tissue samples of EC patients was detected by polymerase chain reaction (PCR) and HPV diagnostic kit. Results. The river water has higher cytotoxicity than the shallow well water and induced significant cell malignant transformation, while deep well water has not shown the malignant cell transformation. In Huaihe River water, the 3-MC concentration was found higher than shallow and deep wells. An HPV infection rate was found high in patients with esophageal cancer. Conclusion. Long-term consumption of polluted water can induce malignant cell transformation, and the presence of HPV may be an important cause of cancer.